2022
DOI: 10.1177/15910199221134307
|View full text |Cite
|
Sign up to set email alerts
|

Repeated mechanical thrombectomy for recurrent large vessel occlusion: A systematic review and meta-analysis

Abstract: Background Mechanical thrombectomy (MT) is the standard treatment for acute large vessel occlusion (LVO). Recurrent LVO can still occur in patients who already underwent MT for the first LVO. This study aimed to evaluate the efficacy of repeating MT for recurrent LVO. Methods This meta-analysis of the available literature was conducted to summarize the current evidence regarding repeated MT outcomes in patients with recurrent LVO. All studies with ≥ 1 outcomes of interest were included. The Newcastle-Ottawa Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Previous nonrandomized studies have shown similar procedural delays whether the access was TRA or TFA in selected patients. 21 Our study has explored the use of the radial artery as a default access for most of patients without including some characteristics that influence usual decisions, such as the type of aortic arch based on the origin of supra-aortic vessels or based on its relationship with the parallel plane perpendicular to the outer curvature of the arch. These elements could explain the discrepancy in results between the SFERA trial and previous studies in terms of procedural delays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous nonrandomized studies have shown similar procedural delays whether the access was TRA or TFA in selected patients. 21 Our study has explored the use of the radial artery as a default access for most of patients without including some characteristics that influence usual decisions, such as the type of aortic arch based on the origin of supra-aortic vessels or based on its relationship with the parallel plane perpendicular to the outer curvature of the arch. These elements could explain the discrepancy in results between the SFERA trial and previous studies in terms of procedural delays.…”
Section: Discussionmentioning
confidence: 99%
“…Median time from arterial puncture to first pass (TRA, 24 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) minutes versus TFA, 20 (17-26) minutes; P=0.007) and from arterial puncture to recanalization (TRA, 44 (32-62) minutes versus TFA, 30 minutes; P=0.030) were longer using radial access.…”
Section: Pp Analysismentioning
confidence: 99%
“…Several randomized clinical trials (RCTs) and meta-analyses have demonstrated that EVT significantly improves functional outcomes and reduces disability compared with medical management alone in these patients. However, despite high rates of recanalization with EVT, a substantial proportion of patients still have poor functional outcomes . Optimization of periprocedural management, including blood pressure (BP) control following successful recanalization, may help further improve outcomes in patients with AIS-LVO undergoing EVT.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite high rates of recanalization with EVT, a substantial proportion of patients still have poor functional outcomes. 4,5 Optimization of periprocedural management, including blood pressure (BP) control following successful recanalization, may help further improve outcomes in patients with AIS-LVO undergoing EVT.…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, neurological disorders are the leading cause of disability and the second leading cause of death, with stroke being the largest cause ( 1 ). With the rapid development of interventional techniques and materials in recent years, endovascular intervention has become a primary treatment for acute ischemic stroke, but even so, intravenous thrombolysis (IVT) is now the important and effective treatment for patients within the 4.5-h time window ( 2 , 3 ). Within 24 h of IVT, a subset of patients may experience a worsening of neurological deficits, which has been described as early neurological deterioration ( 4 ), which has been reported to be associated with poor outcomes ( 5 ).…”
Section: Introductionmentioning
confidence: 99%